A model of a rangeland grazing system within a management procedure approach framework - Soares, Muri (Department of Biological Sciences, 2017)
A model describing livestock grazing system dynamics was developed and fitted to available data. This study preliminarily explored the use of a formal management procedure (MP) approach to determine appropriate annual offtake in a terrestrial system. This approach has been applied in marine systems with great success, but has never been tried in terrestrial ecosystems. Rangelands and marine systems have in common the fact that there is often an offtake component to them and so stakeholders in those systems need knowledge of optimal harvesting strategies within defined management strategies. Three models were developed that described the growth of female goats in Paulshoek. The first (basic livestock model) depicted the growth of livestock as a logistic equation with an adult survival term and an annual growth term. The second model (rainfall-livestock model) added a rainfall component, with livestock productivity modelled as a function of rainfall. The final version of the model (vegetation-rainfall-livestock model) added a vegetation component that interacted with rainfall and livestock. The rainfall-livestock model provided a statistically significant better fit to the data, followed by the vegetation-rainfall model. The vegetation-rainfall-livestock model provided a reasonable representation of livestock population changes through time, with the largest deviations evident over the period 1975-1980. Results show that environmental factors alone are unable to fully explain observed system dynamics because anthropogenic factors for which no data are available may also play a role. Preliminary exploration with a simple MP suggested that a low offtake rate of 10% provided the highest average annual offtake. Our study has shown that a rangeland stocking system can be reasonably described by a simple model that uses only rainfall data and a rainfall-vegetation-livestock interaction. Rangeland livestock systems would benefit greatly from adopting an MP approach as it would allow stakeholders to make informed decisions on stocking rates and annual offtake.